Three-dimensional topological radiogenomics of epidermal growth factor receptor Del19 and L858R mutation subtypes on computed tomography images of lung cancer patients - Kenta, Ninomiya; Hidetaka, Arimura; Kentaro, Tanaka; Chan, Wai Yee; Yutaro, Kabata; Shinichi, Mizuno; Nadia Fareeda, Muhammad Gowdh; Nur Adura, Yaakup; Liam, Chong Kin; Chai, Chee Shee; Ng, Kwan Hoong (ELSEVIER, 2023)
Objectives : To elucidate a novel radiogenomics approach using three-dimensional (3D) topologically invariant Betti numbers (BNs) for topological characterization of epidermal growth factor receptor (EGFR) Del19 and L858R mutation subtypes.